The Effect of Acupressure Massage on Reducing Dysmenorrhea Pain in Female Students at the Darul Hikmah Islamic Boarding School, Medan Islamic Education Park - Saddiyah Rangkuti (International Journal on ObGyn and Health Sciences, 2026)
Dysmenorrhea pain can interfere with a person's productivity, one of which is in teenage students who are still in school, it can have an impact on their productivity in the school environment, not infrequently a student who experiences dysmenorrhea pain has to take a school holiday because of the pain she experiences. One alternative that can be applied when dysmenorrhea pain is acupressure massage. Where this study aims to determine whether there is an effect of Acupressure Massage on Reducing Dysmenorrhea Pain in Female Students of Darul Hikmah Islamic Boarding School, Medan Islamic Education Park in 2024. This study is a quasi-experimental study with a one-group pre-test and post-test approach. The population is all 102 female students of Darul Hilmah Islamic Boarding School, Medan Islamic Education Park, sampling using total sampling with a sample size of 30 people. This research was conducted from June 10 to July 22, 2024. The results of the study showed that the decrease in dysmenorrhea pain in female students before being given acupressure massage at the Darul Hikmah Islamic Boarding School, Medan Islamic Education Park in 2024, the majority experienced moderate pain, and the decrease in dysmenorrhea pain in female students after being given acupressure massage at the Darul Hikmah Islamic Boarding School, Medan Islamic Education Park in 2024, the majority were in mild pain. Based on the results of the paired t test, it was found that the p value = 0.000 <0.05 so it can be concluded that there is an effect of acupressure massage on reducing dysmenorrhea pain in female students at the Darul Hilmah Islamic Boarding School, Medan Islamic Education Park in 2024. The suggestion that can be conveyed from this study is that everyone is able to inform and apply acupressure massage as an alternative to reducing dysmenorrhea pain